PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABELINTERVENING PADA BANK SWASTA NASIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Ramadani, Yana Fitriyah; Wiryaningtyas, Dwi Perwitasari; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aimed to determine the effect of capital structure and liquidity on Company Value with Profitability as an Intervening Variable at National Private Banks Listed on the Indonesia Stock Exchange Period 2019-2021. The population in this study were all National Private Banks listed on the IDX in 2019-2021, which amounted to 46 National Private Banks. This study's sampling technique used purposive sampling, so that 11 samples were obtained, which were used for data analysis. Data analysis and Hypothesis Testing in this study used the Smart PLS 3.0 application. The results of this study show that capital structure has a significant negative effect on Profitability, Liquidity has a negative but insignificant effect on Profitability, while Capital Structure and Profitability have a positive but insignificant effect on Profitability. Profitability, Capital Structure, and Profitability have a positive but insignificant effect on Company Value; Liquidity has a negative but insignificant effect on Company Value, Capital structure, and liquidity have a negative but insignificant effect on company value through Profitability, and liquidity has a negative but insignificant effect on company value through Profitability.